URGENSI ISBAT NIKAH BAGI PERKAWINAN DIBAWAH TANGAN (Studi Kasus Pada Warga di Desa Ciherang Kecamatan Pasawahan Kabupaten Purwakarta) - M Sanusi; Azi Ahmad Tadjudin; Sofia Gussevi (Muttaqien, 2022)
This study aims to describe and how the urgency of itsbat marriage for underhand marriages. This is important to study considering that there are many residents of Ciherang Village, Pasawahan District, Purwakarta Regency who have not received a marriage certificate. This research uses descriptive qualitative method. This approach is based on the consideration that to describe an urgency that occurs in society and of course requires an in-depth description. Based on the results of data analysis, it is concluded that first, the background of the underhand marriage is economic background, pregnancy outside of marriage, and not old enough. Second, the underhand marriage process carried out by the three couples was carried out only with the family and religious leaders. The places where the marriages of the three couples were held were at the residences of the women, men, and religious leaders. Third, the Isbat of marriage is considered very important and useful. Because with marriage isbat, they get a marriage certificate from their marriage so that it can be used for the needs of children and families. Such as the need to make a child's birth certificate, the need to take care of a permit to become a migrant worker and so on.